Konstruksi Pemikiran Merleau-Ponty Tentang Seksualitas: Merleau-Ponty's Construction of Thought on Sexuality - Alfasina, Muhammad Reza (Undiksha, 2025)
The study of the body in philosophy has a central place in Western philosophical thought. The body is often separated from the soul and the separation between the two has long been a topic of discussion in various discourses such as religion, myth and philosophy. In his analysis, Merleau-Ponty's use of the word ‘dimension’ refers to aspects of lived experience without minimising experience during life. One aspect of the dimension is sexuality. This research uses a descriptive qualitative research method using elements of the method, namely: description, interpretation, heuristics that focus on document studies. By explaining descriptively and analysing Maurice Merleau-Ponty's thoughts and theories about sexuality. The purpose of this research is to explore the understanding of sexuality with Merleau-Ponty's theoretical glasses. Based on the description above, the author draws the following conclusions: In Merleau-Ponty's thinking, the schools of intellectualism and in Merleau-Ponty's thinking, the schools of intellectualism and empiricism misunderstand the relationship between perception and consequently fail to understand the relationship between mind and body, self and world, and body and self and world. Humans are supposed to act and seek meaning in the world, the world is not regarded as contemplation but as an active role in the world. as contemplation but actively participating in it.